Regional Fiscal Landscape : Examing the Dynamics of District Balance in the Context of Regional Development - Rineliana, Rineliana; Yohanisti, Yohanisti; Tampubolon, Dahlan; Tampubolon, Omar Farrakhan (Jurnal Ekonomi & Bisnis, 2025)
This research analyzes the dynamics of Indragiri Hulu Regency's financial balance sheet for 2019-2024 and its regional development implications. This study uses a quantitative descriptive approach to examine trends, composition, and economic performance based on solvency ratios and fiscal independence. The results show a shift in asset structure from liquid to illiquid assets, with fixed assets reaching 90.05% by 2024. Significant decreases occurred in current assets by 48.22% (2024) and cash equivalents by 85.95% (2024). Solvency ratios are excellent, with a debt-to-asset ratio below 1% and no long-term liabilities, but fiscal independence remains low (8.2%-11.5%). The Local Revenue Effectiveness Ratio is considered adequate (101.2%), while the financial efficiency ratio is less efficient (100.8%). The research recommends strengthening cash management, adopting asset performance management, reforming receivables management, diversifying revenue, and developing innovative financing strategies to enhance fiscal sustainability and support regional development.